Assemblaga Art and its technical treatments in the productions of students of the Department of Art Education (Journal of the College of Basic Education, 2025)
The era in which postmodern art emerged witnessed the founding beginnings of assemblage art, as artwork became a field for practicing experimentation with new, unconventional materials through the possibility of using them as a kind of formative solutions that stimulate the connoisseur’s thinking and move away from the familiar, abandoning the ideal mental model and using marginalized techniques, means and resources gave a new vision to artistic productions and the emergence of technical methods for processing in artwork, including materials found in the natural, social and cultural environment, and the artist’s style is what gives vitality to his works. These multiple materials and techniques freed artwork from its traditional stillness and made it stimulate thought in both the artist and the art student. The subject of art education seeks to open new horizons for learners through drawing and colouring techniques and their investment in the materials available in the environment and how the student employed them in his artistic works. Hence, the problem of the current research was defined by the following question;Q/ What are the technical treatments for assemblage art in the productions of the students of the Department of Art Education?The current research aims to identify the assemblage art and its technical treatments in the products of the students of the Department of Art Education. The second chapter included two topics: the first was the art of assemblage, meaning and concept, and the second was the technical treatments, in addition to the indicators of the theoretical framework and previous studies. The third chapter included the research community. The researcher reviewed the largest amount of collective works available in the Department of Art Education, College of Fine Arts, University of Baghdad, to benefit from them in a way that covers the research objectives, thus forming the community. As for the research sample, a selective, intentional sample was chosen from the collective works produced by students of the Department of Art Education. To show the results, the researcher used a set of statistical methods, and the most important of these results are; The current research aims to identify the assemblage art and its technical treatments in the products of the students of the Department of Art Education. The second chapter included two topics: the first was the art of assemblage, meaning and concept, and the second was the technical treatments, in addition to the indicators of the theoretical framework and previous,studies. The third chapter included the research community. The researcher reviewed the largest amount of collective works available in the Department of Art Education, College of Fine Arts, University of Baghdad, to benefit from them in a way that covers the research objectives, thus forming the community. As for the research sample, a selective, intentional sample was chosen from the collective works produced by students of the Department of Art Education . To show the results, the researcher used a set of statistical methods, and the most important of these results are ; 2-The artistic productions of art education students are on abstract topics that have no relation to lived reality . The student relied on his fertile imagination and produced formal compositions with a contemporary vision that contributed to building the contemporary painting. The most important conclusions are: 1 - The emergence of different materials and methods of assembling them led to the emergence of new characteristics of art. 2 - The completed works featured techniques of assembly, installation, gluing, welding, plastering, etc., and the students were able to employ these techniques in their works.As for the recommendations: introducing the subject of (Assembly Techniques Art) in the curricula of the Department of Art Education in the Faculties of Fine Arts. Finally, the researcher suggests the following: employing the Arabic letter technically in the art of assembling in handicraft paintings